Generation Z Impulse Buying Analysis on Shopee in Special Region of Jakarta - Intan Kamila Khairunnisa; Sholikhah; Dewi Agustin Pratama Sari (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The rise of e-commerce has made online shopping increasingly convenient, leading consumers to often make purchases driven by emotional factors rather than careful planning. This behavior is characterized as impulsive buying, where decisions are made spontaneously. Understanding the various categories of impulsive buying is essential for companies, as it enables them to tailor marketing strategies effectively. This study focuses on assessing the impulsive buying tendencies of Generation Z consumers in Jakarta’s Special Capital Region while identifying their specific impulsive buying type categories. The research evaluates dimensions such as Pure Impulse Buying, Reminder Impulse Buying, Suggestion Impulse Buying, and Planned Impulse Buying, alongside Cognitive and Affective Aspects. Data was collected through an online questionnaire distributed via Google Forms, targeting 126 Generation Z Shopee users in Jakarta. A quantitative approach was employed, utilizing descriptive analysis, simple tabulation, and mean score calculations. Findings reveal that Generation Z’s impulsive buying level on Shopee is rated as "Agree" and "High." Most respondents fall into the Suggestion Impulse Buying and Planned Impulse Buying categories, with their impulsive purchasing behavior significantly influenced by Affective Aspects. These insights are valuable for Shopee, as they highlight opportunities for developing targeted marketing strategies that can stimulate impulsive buying behavior and ultimately boost sales within this demographic. Understanding these dynamics is crucial for businesses aiming to enhance their engagement with young consumers in the competitive online marketplace.